Improving Teacher Ability in Preparing HOTS Questions Through In-House Training (IHT) at Ngaliyan State Elementary School, Samigaluh, Kulon Progo Regency for the 2021/2022 Academic Year - Rumino Rumino (Universitas Islam Indonesia, 2022)
This School Action Research aims to improve the ability of teachers in preparing questions based on Higher Order Thinking Skills (HOTS) through In-House Training (IHT) activities at SD Negeri Ngaliyan, Samigaluh for the academic year 2021/2022. This research is a school action research conducted in 2 cycles, where each cycle consists of 2 meetings. The implementation steps using research methods/procedures are carried out based on the stages of planning, implementation, observation, and reflection. The subjects of the study were the teachers of SD Negeri Ngaliyan, Samigaluh, Kulon Progo Regency, for the academic year 2021/2022, totaling 8 people consisting of 6 classroom teachers and 2 subject teachers. The results showed that the use of In-House Training (IHT) can improve the ability of teachers in preparing Higher Order Thinking Skills (HOTS) questions. The results of the first cycle of research at the 1st meeting obtained an average score of 3.15 with a percentage of 63.03%. When compared to the results of initial observations before the implementation of IHT, there was an increase of 13.03%. Then, in the first cycle for the second meeting, the average value was 3.58 with a percentage of 71.58%. Cycle II for the 1st meeting obtained an average score of 4.22 with a percentage of 84.30%. Cycle II for the second meeting obtained an average observation result of 4.62 with a percentage of 92.30%. The results of the observations when compared with the results of the second cycle of the 1st meeting there was an increase of; 8.00%. Meanwhile, the ability of the resource persons in delivering the material shows that the results of the observation of the first cycle of actions for the 1st meeting show the ability of the resource persons in delivering the material in the second cycle of the 1st meeting, the resource persons obtained an average score of 85.70 with a percentage of 80.59% or